A Survey on Identifying and Categorizing of Diseases in Rice Plants (International Journal of Food and Nutritional Sciences, 2019)
Utilizing-technology to enhance the cultivation of crucial crops for optimal yield and qualityis a compelling prospect. The focus on automatic plant disease detection is particularlyintriguing, offering the potential for effective monitoring across expansive agricultural fieldsand the automatic identification of diseases based on symptomatic cues in various plantsections.